دور الرِّضا الوظيفي في تحسين الأداء التَّسويقي (دراسة ميدانيَّة على مؤسَّسة الخطوط الحديديَّة السُّورية في محافظة اللَّاذقية) - قاسم سامر; معروف حسن (Latakia University Journal - Economic and Legal Sciences Series, 2018)
هدفت هذه الدِّراسة إلى التَّعرف على العلاقة بين الرِّضا الوظيفي والأداء التَّسويقي في مؤسَّسة الخطوط الحديديَّة السوريَّة في اللَّاذقيَّة, من خلال معرفة أثر كل من التَّرقية, وساعات العمل (برنامج العمل), ومحتوى العمل, وبيئة العمل, وقد اعتمد الباحث على المقاربة الاستنباطيَّة كمنهج عام للبحث, واتباع منهجيَّة المسح, وقام بتوزيع الاستبانة على 290 فرد من كادر العاملين في المؤسَّسة, ومن ثمَّ أجرى دراسة ميدانيَّة بغرض بيان هذه العلاقة, وقد خلصت الدِّراسة إلى وجود علاقة معنوية طرديَّة مقبولة بين الرِّضا الوظيفي والأداء التَّسويقي, ثمَّ قدَّم ملخص لأهم النتائج الَّتي تمَّ التَّوصُّل إليها, حيث كانت النتيجة الرئيسة الأهم هي أنَّ هناك دوراً كبيراً للرِّضا الوظيفي في تحسين الأداء التَّسويقي من خلال الترقية وبرامج العمل ومحتوى وبيئة العمل, ثمَّ تمَّ عرض بعض المقترحات والتَّوصيات لتحسين العلاقة والتي أهمُّها: ضرورة أَنْ تزيد المؤسَّسة من اهتمامها برضا العامل الوظيفي من خلال زيادة تحقيق العدالة في الحصول على الترقية ورفع مستوى توافق سياساتها الخاصة بالترقية مع طموحات عامليها؛ لأَنَّها بذلك ستزيد من الفاعليَّة والكفاءة في أداء المؤسَّسة وتحقيق الربحيَّة, وتحسين حجم مبيعاتها, وتعزيز ولاء عامليها لها. This study aimed to identify the relationship between job satisfaction and marketing performance in the Syrian Railways Establishment in Lattakia. By identifying the impact of each the functional upgrade, working hours (work program), work content, and work environment. The researcher relied on the Deductive Approach as a general method. He follows a survey methodology, and he gave a questionnaire to 290 people of the staff of the institution, He also made a field study to show this relationship, The main result of the study was that there an existence of an acceptable positive correlation between job satisfaction and marketing performance through upgrade, work program, content and work environment, And we provided a summary of the main result that have found out is that the most important role of job satisfaction in improving marketing performance, With the presentation of some of the proposals and recommendations The need for the institution to increase its interest in the satisfaction of the functional factor, through achieving in obtaining promotion and providing material and moral incentives through programs of work and providing independence in work, because it will increase the efficiency and effectiveness in the performance of the institution and achieve profitability, and improve the volume of sales, and enhance the loyalty of its employees.